THE GUARDIANSHIP OF PROPERTY OBLIGATIONS OF PEOPLE WITH SYNDROME : According to Islamic Law - Mukdin, Khairani; Ulfa, Nurul; Zubaidi, Zaiyad (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2023)
This journal discusses the protection of the inheritance of children with Down Syndrome who are unable to manage their assets and themselves as well as how Islamic law reviews the treatment of children with Down Syndrome by the heirs. Forgiveness for children with Down Syndrome is a form of family protection as ordered in the Al-Qur'an as well as in the Child Protection Law. Because people with Down Syndrome cannot take care of themselves, let alone manage their assets, so they need forgiveness from a guardian who is responsible for looking after them. Data was collected through observation and interviews in Padang Tiji District, Pidie Regency, Aceh Province. Forgiveness for Down Syndrome sufferers is not carried out by guardians, but by family members from the female line (sisters/mothers) who are not guardians. Most of the women who provide care are poor. The absence of a guardian here is due to each having a family with an income that is only sufficient for their needs. Protection of the inheritance of Down syndrome sufferers is usually in the form of gardens or rice fields, carried out by managing the garden as usual, planting and harvesting the results while looking after, taking care of, nurturing and paying attention to the child with Down Syndrome. This guardianship and management of inheritance is the source of life for Down Syndrome sufferers as well as their guardians. So the life of a Down Syndrome sufferer can only be lived as it is. Needs in the fields of health and education are very poorly paid attention to. In this situation, other families, especially guardians, should also provide care or at least financial contributions to Down Syndrome sufferers, not just rely on the hopes of one party to protect Down Syndrome sufferers who are categorized as disabled. Because Islamic law requires Muslims to help people with disabilities, care and pay attention to them, especially guardians.